Macrofungi diversity in cork-oak and holm-oak Woodlands in Alentejo (Southern Portugal) - Santos-Silva, Celeste (2011)
With the purpose of contributing to a better knowledge of the Portuguese mycota, a compilation study of the macrofungal diversity of cork-oak and holm-oak woodlands (montado/dehesas) of Alentejo, Southern Portugal was made. This work is based on a series of macrofungi surveys, carried out by the authors, between 2005 and 2011, in six representative sites. Taxonomy and nomenclature follows Kirk et al. (2001) and Kirk (2004-2011). Current species distribution was consulted in: online international and national diversity databases, monographs and other national and international publications. As a result 318 taxa were recorded, 68.9 % in cork-oak and 71.7 % in holm-oak woodlands, with 40.6 % of shared taxa. Concerning trophic strategy, 142 mycorrhizal, 173 saprotrophic and 3 parasites were found. The mycorrhizal/saprotrophic quotient was higher in cork-oak (1.12 ± 0.16) than in holm-oak (0.77 ± 0.14) woodlands. Two orders, Agaricales and Russulales, comprised 81 % of the total identified taxa. There was almost no dissimilarity on the number of taxa per family between cork and holm-oak, except for Amanitaceae and Cortinariaceae, both exhibiting higher values in cork-oak. Of the total taxa, 29 represent new records to Portugal.